Political Affiliation, Probable PTSD, and Symptoms of Depression in Iraq and Afghanistan Combat Veterans: A Pilot Study. Issue 10 (October 2017) - Lating, Jeffrey M.; Moore, Rich A.; Sherman, Martin F.; Kirkhart, Matthew W.; Everly, George S.; Chen, Justin K.
Abstract : Abstract: Ideological commitment of military personnel has been associated with mitigating trauma and protecting mental health. This pilot study assessed whether Democratic and Republican political affiliation differentially predicted probable posttraumatic stress disorder (PTSD) and symptoms of depression in 62 male Iraq and Afghanistan combat veterans. The Liberalism-Conservatism Scale, the PTSD Checklist-Military Version (PCL-M), and the Patient Health Questionnaire–9 (PHQ-9) were assessment measures. Results revealed that Democratic combat veterans had stronger liberal attitudes than Republican combat veterans ( r = 0.95). Moreover, of the 50% of the entire sample higher than the cutoff score of 50 on the PCL-M, 84.8% were Democrats compared with 10.3% of Republicans. On the PHQ-9, 46.9% of Democrats compared with 3.7% of Republicans were higher than the cutoff score of 20. These initial results suggest possible mechanisms of action, including differences in shattered world view assumptions, willingness to disclose emotional concerns, and physiological reactions between Democratic and Republican combat veterans.